THE INFLUENCE OF EDUCATIONAL LEVEL, TEACHING EXPERIENCE, TRAINING AND RESPONSIBILITY ON TEACHERS' WORK PRODUCTIVITY - Sabri, Sabri; Sumardin, Sumardin; Bahar, Lailatul Dzikriyya; Sapura, Eni; Pratiwi, Winta (Yayasan Education and Social Center, 2025)
This research aims to analyze the influence of education level, teaching experience, training and responsibility on teacher work productivity at Ibnu Sina Batam Private Elementary School. The research method used is a quantitative approach with multiple linear regression analysis. The sample in this research was 42 teachers obtained using census techniques. Data was collected through questionnaires and analyzed using SPSS software. The research results show that the level of education, teaching experience, training and responsibility simultaneously have a significant effect on teacher work productivity (Fcount = 1379.988 > Ftable = 2.47, sig. 0.000 < 0.05). Partially, Teaching and Training Experience has a significant effect (tcount = 27,308 and 60,150 > ttable = 1.661, sig. 0.000 < 0.05), while the level of education and responsibility are not significant. The coefficient of determination (R² = 0.983) shows that 98.3% of the variation in work productivity is explained by this variable. Training and teaching experience contribute more dominantly, so it is recommended that schools improve training programs and provide teachers with opportunities to gain more diverse teaching experience to increase work productivity